2017
DOI: 10.7567/jjap.57.01ae07
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of nitrogen-containing diamond-like carbon film by filtered arc deposition as conductive hard-coating film

Abstract: Diamond-like carbon (DLC) films, which are amorphous carbon films, have been used as hard-coating films for protecting the surface of mechanical parts. Nitrogen-containing DLC (N-DLC) films are expected as conductive hard-coating materials. N-DLC films are expected in applications such as protective films for contact pins, which are used in the electrical check process of integrated circuit chips. In this study, N-DLC films are prepared using the T-shaped filtered arc deposition (T-FAD) method, and film proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Notably, the density of the amorphous carbon thin lm decreased even when nitrogen, which is heavier than carbon, was added. It has been reported that the density of amorphous carbon thin lms decreases due to nitrogen doping in various deposition methods, such as sputtering, 24 ltered cathodic vacuum arc (FCVA) deposition, 25 and CVD. [26][27][28][29][30] The previous studies have reported that since C-N bonds are much more vulnerable than C-C bonds to damage by plasma in the chamber, the higher the nitrogen concentration is, the more C-N bonds are broken by plasma, thereby lowering the density of the amorphous carbon lm; this mechanism is consistent with the reason for increased surface smoothness when nitrogen is added to amorphous carbon lms by chemical sputtering effect.…”
Section: Basic Characteristics Of Nitrogen-doped Amorphous Carbon Lmsmentioning
confidence: 99%
“…Notably, the density of the amorphous carbon thin lm decreased even when nitrogen, which is heavier than carbon, was added. It has been reported that the density of amorphous carbon thin lms decreases due to nitrogen doping in various deposition methods, such as sputtering, 24 ltered cathodic vacuum arc (FCVA) deposition, 25 and CVD. [26][27][28][29][30] The previous studies have reported that since C-N bonds are much more vulnerable than C-C bonds to damage by plasma in the chamber, the higher the nitrogen concentration is, the more C-N bonds are broken by plasma, thereby lowering the density of the amorphous carbon lm; this mechanism is consistent with the reason for increased surface smoothness when nitrogen is added to amorphous carbon lms by chemical sputtering effect.…”
Section: Basic Characteristics Of Nitrogen-doped Amorphous Carbon Lmsmentioning
confidence: 99%
“…In the infrared field, the hard DLC film can be also used as the protective and anti-reflective film [6][7][8][9], because of its low optical absorption in the MIR (medium infrared) band of 3∼5 μm. Compared with CVD (chemical vapour deposition), PVD (physical vapor deposition) technology can prepare the non-hydrogenated DLC film with higher hardness and higher chemical inertness [10,11], because the unstable C-H bond is the absence in the DLC film. However, it's difficult to grow the uniform film by PVD onto the large curved substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Electrically conductive hard-coating films are required as a protective film on the tip of a contact pin that is used in the electrical inspection process. [1][2][3] Gold plating, which is the surface protective film of commercial contact pins, has the oxidation prevention of a base metal and high electrical conductivity but poor wear resistance. Also, the protective films of the contact pin are required to have high adhesion resistance for suppressing adhesion of the solder to the tip of the pin during the inspection process.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the protective films of the contact pin are required to have high adhesion resistance for suppressing adhesion of the solder to the tip of the pin during the inspection process. 3) Diamond-like carbon (DLC) films are amorphous structures that have been widely used as protective-coating films because the films have superior properties such as high hardness, high wear resistance, and excellent adhesion resistance. [4][5][6][7] It is thought that a DLC film has sp 2 and sp 3 carbon bonding structures, and its electrical resistivity is high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation